Mapping the Regional Development Disparities in Western Indonesia: An Integrative Approach of Williamson Index and Klassen Typology - Nopiah, Ririn; Barika, Barika; Septriani, Septriani (Tinta Emas Institute, 2024)
Disparities is one of the problems of economic development in developing countries. The Western Region of Indonesia tends to contribute to high economic growth but is accompanied by the problem of regional disparities which is also relatively high. Efforts to reduce regional disparities are aimed at accelerating equitable development. This study examines the development of inter-regional disparities mapping through the Klassen typology method, measuring disparities with the Williamson index in the Western Region of Indonesia in 2021-2023. The results show that most regions are still in the relatively underdeveloped and less developed category and the average regional disparities index is at moderate disparities, namely 0.465. This study provides suggestions to prioritize development based on regional equality, especially areas that are still underdeveloped.